PENGARUH KOMPETENSI DAN KEPERCAYAAN DIRI INVESTOR TERHADAP PERILAKU PERDAGANGAN SAHAM - Okky Putrie Wibisono (Journal of Business & Banking, 2013)
In decision making related to investment, selection process is not an easy job for the investors. This is true when they do it in an uncertainty situation. Besides that, choosing a certain invest- ment asset has its own consequence such as it may be beneficial or the other way around. The purpose of this study is to determine the influence of competence and overconfidence of indi- vidual investor toward the stock trading behavior. This research also uses demographic factors as control variables such as gender, age, income, and educational background. The sample consists of 133 investors of twenty four securities companies in Surabaya and the analysis was done by means of employs Multiple Regression Analysis to test the hypotheses. The results re- veal that investors competence and overconfidence significantly affect their stock trading be- havior. Investor who perceive themselves to be more competence and overconfidence will act on their beliefs by trading more compared by those who less competence and overconfidence. Given the results, brokerage and security firms should understand their investors competence and overconfidence, and take any action to improve them by providing information and educa- tion. By increasing their competence and self-confidence, investors will trade more which will ultimately increase the brokerage and securities firms profits.